Unpacking the Countercyclicality of Post-Secondary Enrollment in the United States - Alena Bicakova; Matias Cortes; Kelly Foley; Jacopo Mazza; Peter McHenry (Institute of Labor Economics (IZA), 2025)
Using data from the Current Population Survey's Education Supplement for 1977-2023, we explore two important, yet understudied facets of the pattern of countercyclical post-secondary education (PSE) enrollment in the U.S. First, we show that economic downturns are associated with higher enrollment probabilities at both 2- and 4-year colleges among young men, but only at 2-year institutions among young women. Second, we show that the overall increase in enrollment propensities during downturns is primarily driven by persistence (i.e., changes in enrollment among individuals with prior PSE participation), rather than matriculation (i.e., new enrollments). However, higher unemployment rates increase matriculation probabilities at 2-year colleges among 18-year-old men and women, and at 4-year colleges among individuals in their early 20s. Our findings improve our understanding of the dimensions along which aggregate economic fluctuations induce changes in human capital acquisition.
Keywords: I23; J24; E32; 330; college enrollment; business cycles; 2- and 4-year institutions; persistence